The α4β1 Homing Pathway Is Essential for Ileal Homing of Crohn's Disease Effector T Cells In Vivo - Zundler, Sebastian; Fischer, Anika; Schillinger, Daniela; Binder, Marie-Theres; Atreya, Raja; Rath, Timo; Lopez Posadas, Rocío; Voskens, Caroline J.; Watson, Alastair; Atreya, Imke; Neufert, Clemens; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
BACKGROUND: The precise mechanisms controlling homing of T effector (Teff) cells to the inflamed gut in Crohn's disease (CD) are still unclear, and clinical outcome data from patients with inflammatory bowel disease treated with the anti-α4β7 integrin antibody vedolizumab suggest differences between ulcerative colitis and CD. METHODS: Expression of homing molecules was studied with flow cytometry and immunohistochemistry. Their functional role was investigated in in vitro adhesion assays and in a humanized mouse model of T cell homing to the inflamed gut in vivo. RESULTS: Despite in vitro blockade of CD Teff adhesion to mucosal vascular addressin cell adhesion molecule-1 (MadCAM-1) and in contrast to previous observations in ulcerative colitis, anti-α4β7 treatment did not result in reduced Teff cell homing to the colon in vivo. However, the integrin α4β1 was expressed in higher levels on Teffs from patients with CD compared with controls, while its expression in the peripheral blood declined, and its expression in the intestine increased during the course of clinical vedolizumab treatment. Consistently, adhesion of CD Teffs to vascular cell adhesion molecule-1 (VCAM-1) was blocked by inhibition of α4 and α4β1 in vitro. Moreover, in vivo homing of CD Teffs to the ileum was reduced by inhibition of α4 and α4β1 integrins, but not α4β7 integrins. CONCLUSIONS: Our findings suggest that Teff cell homing to the ileum through the axis α4β1-VCAM-1 is an essential and nonredundant pathway in CD in vivo, possibly affecting efficacy of clinical treatment with antiadhesion compounds.
EVALuna2:33825